2012
DOI: 10.1038/modpathol.2012.84
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumor cell proliferation in mantle cell lymphoma is associated with elevated insulin-like growth factor 2 mRNA-binding protein 3 expression

Abstract: Mantle cell lymphoma is an aggressive, non-curable B-cell lymphoma, characterized by the translocation t(11;14)(q13;q32) involving CCND1 and a high number of additional genetic alterations. Chromosomal gains of 7p are frequent in mantle cell lymphoma, with insulin-like growth factor II mRNA-binding protein 3 (IGF2BP3 aka IMP3) being the most upregulated gene in this region. IGF2BP3 is a member of the IGF II mRNA-BP family, and increased IGF2BP3 expression is associated with an aggressive behavior in many malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…(B) The same analysis using the epithelial and mesenchymal signatures from the meta-analysis by Groger et al [18]. [35,36]. Our HSC microarray analysis confirmed that expression of Igf1R and Igf2bp1 both increase in parallel with Igf2bp3 as mouse Q-HSC differentiate into MF (Fig.…”
Section: Igf2bp3 Promotes Mf-hsc Growth and Proliferation By Stabilizsupporting
confidence: 62%
“…(B) The same analysis using the epithelial and mesenchymal signatures from the meta-analysis by Groger et al [18]. [35,36]. Our HSC microarray analysis confirmed that expression of Igf1R and Igf2bp1 both increase in parallel with Igf2bp3 as mouse Q-HSC differentiate into MF (Fig.…”
Section: Igf2bp3 Promotes Mf-hsc Growth and Proliferation By Stabilizsupporting
confidence: 62%
“…Like p53 expression, tumors with high Ki-67 PI more frequently showed IMP3 expression. This observation has been documented in other tumors like hepatocellular carcinoma, B cell lymphoma, meningioma, and bile duct carcinoma 14,27,28,29. With these findings, IMP3 is considered to be a better prognostic marker than p53 or Ki-67 and these three proteins may be closely connected.…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, it is tempting to speculate that IGF2BP3 is a direct transcriptional target of MLL fusion proteins. However, IGF2BP3 is also overexpressed in most of the B-ALL cell lines tested, various mature B cell neoplasms (34)(35)(36)(37), and a number of epithelial malignancies. Furthermore, differential regulation of this protein has been observed in B-ALL (38).…”
Section: Discussionmentioning
confidence: 99%